2021
DOI: 10.3390/nu13061905
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Metabolite Modifications after Dietary Exclusion of Dairy Products and Reduced Consumption of Fermented Food in Young and Older Men

Abstract: The gut microbiota adapts to age-related changes in host physiology but is also affected by environmental stimuli, like diet. As a source of both pre- and probiotics, dairy and fermented foods modulate the gut microbiota composition, which makes them interesting food groups to use for the investigation of interactions between diet and ageing. Here we present the effects of excluding dairy products and limiting fermented food consumption for 19 days on gut microbiota composition and circulating metabolites of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 85 publications
(97 reference statements)
1
13
0
Order By: Relevance
“…In addition, the less efficient production of primary bile acids in the liver ( 35 ) and the modified gut microbiota composition during aging ( 57 ) could explain the lower levels of glycocholic acid observed in the OA group in the present study. However, our previous study with the same study individuals revealed that there were no significant differences in gut microbiota profile between the YA and the OA groups ( 26 ), suggesting the less efficient production of primary bile acids in the liver could be the major factor of the lower glycocholic acid levels in the OA group. Lipid metabolism was particularly influenced by age, presenting delayed t max of dodecanoic acid (C12:0), myristic acid (C14:0), and acylcarnitines in the OA group.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, the less efficient production of primary bile acids in the liver ( 35 ) and the modified gut microbiota composition during aging ( 57 ) could explain the lower levels of glycocholic acid observed in the OA group in the present study. However, our previous study with the same study individuals revealed that there were no significant differences in gut microbiota profile between the YA and the OA groups ( 26 ), suggesting the less efficient production of primary bile acids in the liver could be the major factor of the lower glycocholic acid levels in the OA group. Lipid metabolism was particularly influenced by age, presenting delayed t max of dodecanoic acid (C12:0), myristic acid (C14:0), and acylcarnitines in the OA group.…”
Section: Discussionmentioning
confidence: 74%
“…Not only the levels of these metabolites 24 h after the dairy challenge are still low, but their levels actually increased during the run-in period. The postprandial behavior of these lipids is complex as likely influenced by the fermentation of milk, processing by the gut microbiota and systemic metabolism ( 26 ). A more detailed discussion of these molecules would request that their molecular structure be precisely determined by high resolution GC-FID ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several FFA groups were determined based on the sums of individual FFAs (Table S2). Immediately prior to analysis, plasma samples were thawed on ice and were prepared for analysis by adding 15 µL of the internal standard (C13, 7 µg/15 µL) to 100 µL of plasma, followed by methylation of FFAs with MeOH/HCl at 25 °C for 45 min using methods described previously [ 46 , 47 ]. A post-reaction treatment for neutralization was performed with 350 µL Na 2 CO 3 , and extraction was performed with 300 µL hexane.…”
Section: Methodsmentioning
confidence: 99%